2008
DOI: 10.1093/socrel/69.2.187
|View full text |Cite
|
Sign up to set email alerts
|

How Denominational Resources Influence Debate about Homosexuality in Mainline Protestant Congregations*

Abstract: A growing body of research examines national conflicts over homosexuality in mainline Protestant denominations, but few studies have explored the concrete ways individual congregations are responding. We focus on thirty mainline Protestant congregations (in the Evangelical Lutheran Church in America, the Presbyterian Church [U.S.A.], and the United Methodist Church) in the northeastern United States that have formally considered the issue of homosexuality recently. Based on in-depth, semi-structured interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 34 publications
1
44
1
Order By: Relevance
“…Research (Cadge, Olson & Wildeman, 2008;Sherkat, de Vries, & Creek, 2009;Van Geest, 2007) has shown Protestant, evangelical religious affiliation plays a major role in shaping individuals' attitudes about the morality of homosexuality. Adamczyk and Pitt (2009) …”
Section: Christianity and Instructional Leadership = Social Justice Lmentioning
confidence: 99%
“…Research (Cadge, Olson & Wildeman, 2008;Sherkat, de Vries, & Creek, 2009;Van Geest, 2007) has shown Protestant, evangelical religious affiliation plays a major role in shaping individuals' attitudes about the morality of homosexuality. Adamczyk and Pitt (2009) …”
Section: Christianity and Instructional Leadership = Social Justice Lmentioning
confidence: 99%
“…Whether it is a instructed via the Bible, the Koran, or the Torah, fundamentalists believe that their practice of faith is undeniably the truth and that all other beliefs or interpretations are false (Cadge et al, 2008;Whitehead, 2010). Many fundamentalists justify their beliefs as a cause that is sanctioned by a higher being (Rowatt & Franklin, 2005;Whitehead, 2010), and their unquestioning acceptance of "truth" often stems from fear of losing salvation or fear that nonbelievers will threaten traditional values with nonadherent lifestyles (Laythe, Finkel, & Kirkpatrick, 2001).…”
Section: Religious Fundamentalismmentioning
confidence: 99%
“…Despite the national attention gay, lesbian, and bisexual issues receive in the United States, little research can be found on religious affiliation and the development of prejudicial attitudes (Cadge et al, 2008). Contemporary studies have focused on congregations, mainly in the Protestant faith (Cadge, 2002;Djupe & Gilbert, 2003).…”
Section: Religious Affiliationmentioning
confidence: 99%
See 1 more Smart Citation
“…An individual's failure to reconcile his or her sexual identity and spiritual and/or religious heritage can cause depression, low self-esteem, alienation from family and friends, and other significant consequences (Love, Bock, Jannarone, & Richardson, 2005;Martell, Safren, & Prince, 2004;McQueeney, 2009). Many religious traditions espouse strict opposition in theology and policy to healthy and normative integration of affectional orientation into one's religious affiliation (Cadge, 2008;Cohen, Aviv, & Kelman, 2009;Crowley, 2008). Furthermore, many religious institutions treat sexual minority members in their churches, synagogues, and mosques as invisible.…”
Section: Religious Aspects Of Homoprejudice and Its Impact On Lgb Spimentioning
confidence: 99%